Sport, Leisure and Culture in Twentieth-Century Britain - Metcalfe, Alan (Labour / Le Travail, 2003)
The article reviews the book, "Sport, Leisure and Culture in Twentieth-Century Britain," by Jeffrey Hill.
Keywords: BOOKS -- Reviews; HILL, Jeffrey; Nonfiction; SPORT, Leisure & Culture in 20th Century Britain (Book); Sports